Suprascapular Nerve Block in Chronic Shoulder Pain: A Review - Reis e Silva, Miguel; Serviço de Medicina Física e Reabilitação, Centro Hospitalar Lisboa Central, Lisboa, Portugal (2019)
Introduction: The goal of this study was to find the existing evidence about the suprascapular nerve block in chronic shoulder pain. Methods: The term “suprascapular nerve block” was searched at PubMed, in October 2015, with 156 analyzed articles. The inclusion criteria were experimental studies with non-continuous suprascapular nerve blocks in patients with chronic shoulder pain not surgery-related.Results: After the application of the inclusion/exclusion criteria, 8 studies were selected: 7 randomized controlled trials and 1 case series. Of these trials, only 2 were placebo controlled with saline injection. The most frequent pathologies were adhesive capsulitis, hemiplegic shoulder pain and glenohumeral osteoarthritis. The procedures were guided by ultrasound, electromyography or anatomy landmarks and the most frequent drugs used were a mixture of bupivacaine and metilprednisolone. All the studies reported significant improvements in pain and range of motion scores (p < 0.05), which are analyzed.Discussion: There are multiple variations among the studies, from the number of injections (1-3), the drugs used (with or without corticosteroid), the studied pathologies and the control groups. However, across all the studies there is a longitudinal improvement in patient’s pain and range of motion scores.Conclusion: Suprascapular nerve block may be an effective treatment in chronic shoulder pain. Additional quality studies are needed to find in which pathologies it may be useful and which are the most efficient injected drugs and treatment regime.